A checklist of oligochaetes (Annelida) from Taiwan and its adjacent islands - Tsai, Chu-Fa; Shen, Huei-Ping; Tsai, Su-Chen; Lin, Kang-Jieh; Hsieh, Hwey-Lian; Yo, Shao-Pin (Zootaxa, 2009)
This checklist lists 98 species and subspecies of oligochaetes (Annelida) that have been reported so far as members of the natural fauna of Taiwan and its adjacent Lanyu (Botel Tobago), Gueishan (Turtle) and Penghu (Pescadore) Islands. Terrestrial oligochaetes have been studied for over a century since 1898, particularly intensively in the past ten years. They are represented by 72 species of which 42 (58.3%) species and subspecies are endemic to Taiwan. They belong to the families Moniligastridae, Glossoscolecidae, Lumbricidae, Octochaetidae, Ocnerodrilidae, and Megascolecidae. Megascolecidae is the most dominant family with 63 species, comprising 87.5% of the terrestrial Taiwanese earthworms reported so far. Aquatic oligochaetes have been investigated for about a decade since 1995, and are represented by 26 species. Of them, 25 are in the family Naididae (including Tubificidae) and Eiseniella tetraedra in the family Lumbricidae.